ENABLING THE TRADE OF VAPERS ACCORDING TO RESOLUTION 153/21 OF THE D.N.V.S. - Adrián Cabrera Rodas, César; Graciela Cáceres Santacruz, María; Gomes de Moura, Lucas (Revista Gênero e Interdisciplinaridade, 2023)
The research work carried out is entitled “Enabling the trade of vapers according to resolution 153/21 of the D.N.V.S., it identifies the legal process of authorization that must be carried out by commercial and exporting companies of products related to vapers based on the resolution. The quantitative approach was taken with a descriptive level and for this, 55 businessmen and company representatives have been taken as a sample to apply the data collection instrument that was the survey. It was possible to conclude that most of the companies are not in a position to enable their premises in light of the new resolution, by which employers must take measures and make some modifications if they wish to achieve said enablement.